Full-dimensional quantum calculations of the vibrational states of H5+ - Song, Hongwei (2013)
Full-dimensional quantum calculations of the vibrational states of H5+ have been performed on the accurate potential energy surface developed by Xie et al. [J. Chem. Phys. 122, 224307 (2005)]. The zero point energies of H5+, H4D+, D4H+, and D5+ and their ground-state geometries are presented and compared with earlier theoretical results. The first 10 low-lying excited states of H5+ are assigned to the fundamental, overtone, and combination of the H2–H3+ stretch, the shared proton hopping and the out-of-plane torsion. The ground-state torsional tunneling splitting, the fundamental of the photon hopping mode and the first overtone of the torsion mode are 87.3 cm −1, 354.4 cm −1, and 444.0 cm −1, respectively. All of these values agree well with the diffusion Monte Carlo and multi-configuration time-dependent Hartree results where available.